Community Service “Guidance on Governance and Accounting Recording using Ms.Excel in The Si Kunyit Jamu Business Group in Denpasar” - Indriyani, Ni Made Vita; Ade Ruly Sumartini, Ade Ruly Sumartini; I Wayan Gde Yogiswara Darma Putra, I Wayan Gde Yogiswara Darma Putra (EQUATOR SINAR AKADEMIA, 2024)
Indonesia is an agricultural country that has great potential and abundant natural resources for agricultural products. However, from this potential, the economic problems faced by rural communities, the majority of whom are farmers, are very diverse, especially when the Covid-19 pandemic occurred, causing people to look for ways to find additional income due to the large number of layoffs. This is also the first step for the Si Kunyit Herbal Medicine Business Group in utilizing the spices they have and becoming a booster during the pandemic. Some of the obstacles faced by the Si Kunyit herbal medicine business group are 1)Not yet having bookkeeping or records related to income, expenses, production costs and profit and loss, 2) Not yet having good governance, so not yet able to set appropriate prices, 3) Marketing systems such as websites, social media and offline marketing that have not been used optimally to market the products produced. 4) Making labels/brands for products to be marketed. 5) Packaging is not yet attractive so it is still inferior to competitors.